VOKAL NASAL BAHASA ACEH DALAM KAMUS KEMARITIMAN ACEH-INDONESIA - Rusli, Herman; Wildan, NFN; Nuthihar, Rahmad; Mukhlis, NFN (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
This article discussed the distribution of nasal vowels in the Acehnese language in the Maritime Dictionary of Aceh-Indonesia. The nasal vowels included were /ã/, /ĩ/, /ũ/, /ɛ/̃, /ɔ̃/, /ʌ/̃, and /ɯ̃/. The data source for this research was the Aceh-Indonesia Dictionary, published by the Aceh Provincial Language Center, Ministry of Education and Culture Research and Technology, in 2021. This study employed a phonological approach with the theory of distinctive features. The research detailed the distribution of nasal vowels, including their frequency of occurrence and syllable positions. To achieve high accuracy in terms of nasal vowel occurrence frequency and syllable positions, the data was processed using the Antconc software. The research findings showed that maritime domain nasal vowels in the Acehnese language consisted of noun (n) and verb (v) word classes. There were eight nasal vowels in the noun class and two nasal vowels in the verb class. Among all nasal vowels in the Acehnese language, the vowels /ɛ/, /ɔ̃/, and /ɯ̃/ were not found in the Maritime Dictionary of Aceh-Indonesia. The research results also demonstrated that some nasal vowels were formed due to reduplication and onomatopoeia. In terms of syllable position, Acehnese nasal vowels were only found in the middle and at the end of syllables. Nasal vowels in the initial syllable position of the Acehnese language could not form words related to maritime matters. Consequently, it could be concluded that nasal vowels were not productive in the maritime vocabulary of the Acehnese la-nguage.Artikel ini membahas distribusi vokal nasal bahasa Aceh dalam Kamus Kemaritiman Aceh-Indonesia. Vokal nasal dimaksud meliputi /ã/, /ĩ/, /ũ/, /ɛ/̃, /ɔ̃/, /ʌ/̃, dan /ɯ̃/. Sumber data penelitian ini adalah Kamus Aceh-Indonesia yang diterbitkan oleh Balai Bahasa Provinsi Aceh, Kemdikbudristek, tahun 2021. Penelitian ini menggunakan pendekatan fonologi dengan teori fitur distingtif. Penelitian ini menjabarkan distribusi vokal nasal yang meliputi frekuensi kemunculan vokal nasal dan melihat posisi silabel. Untuk memperoleh hasil keakuratan yang tinggi terkait frekuensi kemunculan vokal nasal dan posisi silabel, data diolah dengan perangkat lunak Antconc. Hasil penelitian memperlihatkan bahwa vokal nasal bidang kemaritiman dalam bahasa Aceh terdiri atas kelas kata nomina (n) dan verba (v). Terdapat delapan vokal nasal pada kelas nomina dan dua vokal nasal pada kelas verba. Dari semua vokal nasal dalam bahasa Aceh, vokal /ɛ/, /ɔ̃/, dan /ɯ̃/ tidak ditemukan dalam Kamus Kemaritiman Aceh-Indonesia. Hasil penelitian ini juga memperlihatkan bahwa beberapa vokal nasal terbentuk akibat reduplikasi dan onomatope. Ditinjau dari posisi silabel, vokal nasal bahasa Aceh hanya berada di tengah silabel dan di akhir silabel. Vokal nasal pada posisi awal silabel bahasa Aceh tidak dapat membentuk kata yang berkaitan dengan kemaritiman. Dengan demikian, dapat disimpulkan bahwa vokal nasal tidak produktif dalam perbendaharaan kosakata bahasa Aceh bidang maritim.